New algorithms for identifying the flavour of B0 mesons using pions and protons - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (The European physical journal. C, Particles and fields, 2017)
Two new algorithms for use in the analysis of pppppp collision are developed to identify the flavour of B0B0B ^0 mesons at production using pions and protons from the hadronization process. The algorithms are optimized and calibrated on data, using B0→D−π+B0→D−π+{B ^0} \!→ D^{-}π ^{+} decays from pppppp collision data collected by LHCb at centre-of-mass energies of 7 and 8 TeV . The tagging power of the new pion algorithm is 60% greater than the previously available one; the algorithm using protons to identify the flavour of a B0B0B ^0 meson is the first of its kind.